A model of intersectoral flow of technology using technology and innovation flow matrices. Issue 2 (3rd April 2018) - Harada, Tsutomu
ABSTRACT: This paper builds a simple general equilibrium model that sheds new light on the mechanism of intersectoral flows of technology. It explicitly models the production of technology using diverse technology components as inputs. The model shows that demand shocks do not cause innovation while technology shocks as deviations from a balanced growth path induce asymmetric productivity changes across sectors. We also conduct a simple quantitative analysis using recent Japanese R&D data, which shows that most productivity effects remain within the bounds of the sector. We find some important exceptions to this rule, however, in particular for shocks occurring in information technology and precision instruments.